Prognostic value of lymphocyte cell ratios in peritoneal dialysis - Marques,Roberto C. (2021)
ABSTRACT Background: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been introduced as useful inflammatory markers to predict the outcome of a wide spectrum of diseases, such as malignancies and cardiovascular pathologies. Limited evidence is available for their role in end-stage renal disease and dialysis patients. The aim of this study was to evaluate NLR and PLR as predictors of mortality in peritoneal dialysis (PD) patients. Methods: In this retrospective study 122 incident PD patients between 2004 and 2019 were included. Demographic, clinical and laboratory data were collected. Relationships between NLR, PLR and high-sensitivity C-reactive protein (hs-CRP) were evaluated by Spearman correlation test. Univariable and multivariable Cox regression analysis were performed to determine the association of NLR and PLR with all-cause mortality. Results: Mean levels of NLR and PLR were 3.99±2.6 and 195.5±101.7, respectively. Both NLR and PLR were significantly and positively correlated with serum hs-CRP levels (r=0.340, p<0.001 and r=0.360, p<0.001, respectively). The overall mortality rate was 18.9% after a mean follow-up of 30.2±24.0 months. On multivariable modeling, we found that higher NLR (HR=1.662, 95%CI 1.117-2.472) and higher PLR (HR=1.010, 95%CI 1.004-1.015), in addition to lower residual renal function and higher Charlson comorbidity index were significant independent predictors of poor survival, when adjusted for nutritional status. Discussion: In this study, NLR and PLR were validated as inflammatory markers and predicted survival in our PD patients. Our results suggest that NLR might be a better indicator of mortality than PLR.